Словацькі погляди на Україну (1880 – 1914 рр.) - Гучкова, Д.І. (Слово і Час, 2019)
Українські теми в словацькому контексті впродовж 1880 – 1914 рр. виявлялися у трьох
напрямках: 1) слов'янофільський напрямок (ідеологічні, історичні, лінгвістичні, етнологічні,
конфесіональні та культурні аспекти проблематики Росії та східних слов'ян), 2) документально-фактографічний напрямок (подорожні нотатки) тa 3) літературний напрямок (переклади творів українських письменників тa інформація про українське літературне життя в словацькій
літературній публіцистиці). Ці напрямки перепліталися, але найвагомішою була ідеологічна
концепція слов'янської взаємності, яка принципово визначала характер словацьких поглядів
на українське церковне життя, емансипаційний рух, особисто пережиті реалії та літературу.
Поступове прийняття української національної ідентичності, яка викарбовувалася, стало справою пізнішого періоду. The Ukrainian themes appeared in the Slovak context of the period 1880–1914 within three
thematic lines: 1) the Slavophilic line (a wide complex of ideological, historical, linguistic, ethnological,
confessional and cultural issues concerning Russia and Eastern Slavs); 2) the documentary factual line
(travelogue narratives); and 3) the literary line (translations of Ukrainian literary works and information
about the Ukrainian literary life in the genres of literary journalism). These lines overlapped, but the first
one, i.e. ideologically-based line of Slavic solidarity, was the most significant. This line substantially
determined the nature of the Slovak views on the Ukrainian religious life, emancipation movement
(in correlation ‘Little Russia’ – ‘Great Russia’), institutions, personally witnessed affairs and also the
Ukrainian literature. In terms of the conservative national discourse, the Ukrainian independence
movement was represented as a manifestation of separatism and the distinct Ukrainian nationality was
rejected or questioned. Its acceptance was a matter of the later period. The interliterary contacts were
sporadic and occasional. At the beginning of the 20th century, under the influence of the modernization
and liberal attitude of the rising generation to the right of self-determination, the Ukrainian literature was
primarily perceived as a literature of a close Slavic nation, which was, as well as the Slovak nation,
in the position of an oppressed ethnic group lacking its own political independence.